Angel Catbird - Atwood, Margaret, 1939-; Christmas, Johnnie; Bonvillain, Tamra; Piekos, Nate (2016)
"On a dark night, young genetic engineer Strig Feleedus is accidentally mutated by his own experiment when his DNA is merged with that of a cat and an owl"--
Subtitle on volume 2: To Castle Catula. Subtitle on volume 3: The catbird roars.
Keywords: Graphic novels; Superheroes -- Fiction; Genetic engineering -- Fiction; Adventure and adventurers -- Fiction; COMICS & GRAPHIC NOVELS / Superheroes; COMICS & GRAPHIC NOVELS / General; FICTION / Action & Adventure; Graphic novels